The influence of factors characterizing the performance of ports, measured by operational, financial and efficiency indicators - Caldeirinha, Vitor (2022)
The purpose of this study is to analyze the performance of a port through its characterizing factors and understand their importance. Both Data Envelopment Analysis (DEA) and statistics of factor analysis were used, as well as linear regression. Based on a sample of 43 European ports, the results of this study indicate the existence of a relationship between performance and several variables that characterize the port. Additionally, they also confirm the impact of location, governance, size, infrastructure, specialization, logistic integration and maritime services in the ports operational and financial performance and efficiency.